Bacterial Cellulose for Scalable and Sustainable Bio-Gels in the Circular Economy - Giovanni Venturelli; Federica Villa; Mariagioia Petraretti; Giuseppe Guagliano; Marinella Levi; Paola Petrini (Gels)
Microbial-derived materials are emerging for applications in biomedicine, sensors, food, cosmetics, construction, and fashion. They offer considerable structural properties and process reproducibility compared to other bio-based materials. However, challenges related to efficient and sustainable large-scale production of microbial-derived materials must be addressed to exploit their potential fully. This review analyzes the synergistic contribution of circular, sustainable, and biotechnological approaches to enhance bacterial cellulose (BC) production and fine-tune its physico-chemical properties. BC was chosen as an ideal example due to its mechanical strength and chemical stability, making it promising for industrial applications. The review discusses upcycling strategies that utilize waste for microbial fermentation, simultaneously boosting BC production. Additionally, biotechnology techniques are identified as key to enhance BC yield and tailor its physico-chemical properties. Among the different areas where cellulose-based materials are employed, BC shows promise for mitigating the environmental impact of the garment industry. The review emphasizes that integrating circular and biotechnological approaches could significantly improve large-scale production and enhance the tunability of BC properties. Additionally, these approaches may simultaneously provide environmental benefits, depending on their future progresses. Future advancements should prioritize circular fermentation and biotechnological techniques to expand the potential of BC for sustainable industrial applications.